Investigating the level of compliance between sustainability reports and GRI standards in health companies - Aran Erden; Mehmet Arslan; Bora Topal (Afyon Kocatepe Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Nowadays, sustainability is an important concept for people to use and manage social structures, economic activities, and natural resources in a sustainable manner. In this respect, it is necessary for companies to adopt sustainability principles and to examine the compliance of their sustainability reports with GRI (Global Reporting Initiative) standards, which provide a globally accepted framework. The present study aims to determine the level of compliance of the sustainability reports prepared by healthcare companies traded in Borsa Istanbul (BIST) with GRI standards, determine the differences, and investigate the reasons behind them. For this purpose, interview forms, which are frequently used in qualitative research methods, were used to obtain data. A total of seven different business managers who were authorized to prepare the sustainability reports of the enterprises were interviewed through a semi-structured interview form, and the data obtained was analyzed using the CATMA 7 (Computer Assisted Text Markup and Analysis) program. The analysis determines a set of deficiencies pursuant to GRI standards. The interviewed managers state that there is a need for support in inadequate training, failure to update the standards in a timely manner, providing flexibility in reports, and providing incentives from the public sector.